Analisis Tingkat Pengetahuan dan Perilaku Swamedikasi Diare Selama Pandemi Covid-19 - Filomina Dila Putri; Shoma Rizkifani; Hariyanto IH (State University of Gorontalo, 2022)
Diarrhea was determined as one of the Covid-19 symptoms and during the Covid-19 pandemic in 2020, the prevalence of diarrhea increased to 13.05% in district of Rasau Jaya. The limitations of health services during the Covid-19 pandemic led to the increasing of self-medication behavior, including self-medication to overcome those diarrheal symptoms. The object of this study was to determine the level of knowledge and behavior of self-medication for diarrhea in district of Rasau Jaya and the correlation between these knowledge and behavior. We use a cross sectional approach with total of 70 respondents and we use purposive sampling with a questionnaire measuring instrument for sampling technique as well. Data were measured by statistical tests of Spearman rank correlation. The results showed that 57.14% of respondents have a good level of self-medication knowledge whereas 41.43% and 1.43% of respondents have medium and deficient knowledge, respectively. These results are in line with self-medication behavior that shown 95.71% of respondents have a good level of behavior but only 4.29% of respondents have a deficient level. We found that People in Rasau Jaya had a good level of self-medication knowledge and behavior and there is a correlation between those two.